Skeletal stability after 2-jaw surgery via surgery-first approach in facial asymmetry patients using CBCT - Dae Seok Hwang; Jeong Seok Seo; Hong Seok Choi (SpringerOpen, 2020)
Abstract Background The purpose of this study is to compare the skeletal stability of two-jaw surgery via surgery-first approach with conventional two-jaw surgery in facial asymmetry patients by measuring the skeletal changes after surgery from a three-dimensional analysis. From January 2010 to January 2014, 40 patients with facial asymmetry who underwent two-jaw surgery in Pusan National University Hospital were included in this study. They were classified into experimental group (n = 20) who underwent two-jaw surgery via surgery-first approach and control group (n = 20) who underwent conventional two-jaw surgery. After selection of 24 landmarks and the construction of horizontal and sagittal, coronal reference planes, changes in 10 linear measurements and 2 angular measurements were compared between the surgery-first approach and conventional groups in the preoperative, immediate postoperative, and postoperative periods. The paired t test and Student t test were used for statistical analysis. The mean and standard deviation of the measurement were calculated for the experimental and control groups. Results The statistical analysis showed that changes in skeletal measurements were similar between the surgery-first approach and conventional groups, according to each period. However, U1-SRP measurement showed statistically significant changes in surgery-first approach groups at postsurgical change (T1 to T2). Also, the mean treatment duration in the treatment group was 15.9 ± 5.48 months whereas that in the control group was 32.9 ± 14.05 months. Conclusion In facial asymmetry patients, similar results were observed in the postoperative skeletal stability when 2-jaw surgery via surgery-first approach was compared with conventional 2-jaw surgery. However, significant lateral deviation of upper incisor midline was observed. In addition, a shorter average treatment duration was observed. To stabilize the unstable occlusion after surgery, increased wearing of the stent and proactive rubber guidance will be needed.